Spain : 2016 Article IV Consultation-Press Release; Staff Report; Informational Annex; Staff Statement; and Statement by the Executive Director for Spain. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights that Spain's economy has continued its recovery. Real GDP expanded by 3.2 percent in 2015 with the same growth rate expected for 2016, despite a prolonged period of domestic political uncertainty. Nearly 1.1 million jobs were created over the past two years. The rebound in private consumption, exports, and investment, aided by past reforms, has remained the main driver of growth. The current account is projected to record its fourth consecutive annual surplus. Private sector balance sheets have further strengthened, while public debt remains high at about 100 percent of GDP. Real GDP growth is projected to moderate to 2.3 percent in 2017.